2019
DOI: 10.1186/s12880-019-0350-4
|View full text |Cite
|
Sign up to set email alerts
|

Velopharyngeal closure analysis using four-dimensional computed tomography: a pilot study of healthy volunteers and adult patients with cleft palate

Abstract: Background Nasopharyngoscopy is a common method to evaluate velopharyngeal closure in patients with cleft palate. However, insertion of a fiberoptic nasopharyngoscope causes discomfort in patients. The aim of this study was to estimate the reliability of short-time exposure images obtained using 320-row area detector computed tomography (320-ADCT) as a novel evaluation method for the assessment of velopharyngeal function. Methods We evaluated five healthy adult voluntee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 14 publications
1
12
2
Order By: Relevance
“…The VPC patterns were evaluated as circular and circular with Passavant's ridge; however, two patients had unevaluable images. This nding was similar to the assessment of adult postoperative cleft patients reported in our past study: four patients had the circular pattern and one patient had the circular with Passavant's ridge pattern [2]. However, some participants in the current study demonstrated compensatory behavior during blowing to overcome the malfunction.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The VPC patterns were evaluated as circular and circular with Passavant's ridge; however, two patients had unevaluable images. This nding was similar to the assessment of adult postoperative cleft patients reported in our past study: four patients had the circular pattern and one patient had the circular with Passavant's ridge pattern [2]. However, some participants in the current study demonstrated compensatory behavior during blowing to overcome the malfunction.…”
Section: Discussionsupporting
confidence: 90%
“…In that study, we evaluated 10 adult volunteers, which included ve patients with postoperative cleft. We concluded that nasopharyngoscopy and 4D evaluation with 320-ADCT had a high concordance rate for evaluating VPI (8/10 patients) and VPC patterns (9/10 patients) [2].…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations